PENGARUH PELAKSANAAN KEBIJAKAN LAYANAN BIMBINGAN KONSELING SISWA TERHADAP MANAJEMEN PEMBELAJARAN UNTUK MEWUJUDKAN PRESTASI BELAJAR SISWA - Rismayanti, Santi; Ijudin; Munawaroh, Nenden (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the phenomenon of suboptimal student learning achievement at Madrasah Tsanawiyah (MTs) Al-Musaddadiyah Garut, which is characterized by a downward trend in academic attainment alongside low student motivation and affective development. This condition indicates that the implementation of guidance and counseling service policies has not been optimally integrated into learning management. The study aims to analyze the influence of guidance and counseling service policy implementation on learning management, the influence of these policies on learning achievement, and the influence of learning management on student learning achievement. The research method employed is a quantitative approach with a survey method. The population consists of all teachers at MTs Al-Musaddadiyah Garut, with a total sampling of 30 respondents. Data were collected through Likert-scale questionnaires and analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) via the SmartPLS application. The results show that the implementation of guidance and counseling service policies has a positive and significant effect on both learning management and student learning achievement. Furthermore, learning management is proven to have a positive and significant effect on student learning achievement. The coefficient of determination (R²) values of 0.630 for learning management and 0.730 for learning achievement indicate that the model possesses strong explanatory power. Based on these findings, it can be concluded that the effective integration of guidance and counseling services within learning management is crucial for improving student learning achievement holistically. It is recommended to strengthen the collaboration between subject teachers and guidance counselors as a key strategy in madrasah educational management.